Enhanced targeting of CML stem and progenitor cells by inhibition of porcupine acyltransferase in combination with TKI - Agarwal, Puneet (Blood, 2017)
Tyrosine kinase inhibitor (TKI) treatment of chronic myeloid leukemia (CML) has limited efficacy against leukemia stem cells (LSC) responsible for disease propagation, and most CML patients require continued TKI treatment to maintain remission. LSC maintenance is related, at least in part, to signals from the bone marrow microenvironment (BMM). Our previous studies have shown that Wnt signaling from the BMM contributes to preservation of CML LSC following TKI treatment. Secretion of Wnt ligands requires their modification by the O-acyl transferase Porcupine (PORCN). Here we investigated the activity of a potent and selective PORCN inhibitor, WNT974, against CML stem and progenitor cells. WNT974 efficiently antagonized Wnt signaling in human CML CD34(+) cells, and in combination with the TKI nilotinib (NIL) significantly enhanced inhibition of proliferation and colony-forming potential of CML stem and progenitor cells and reduced their growth in immunodeficient mice in vivo, in comparison with NIL alone. Treatment of transgenic CML mice in vivo with NIL in combination with WNT974 significantly reduced leukemic stem and progenitor cell numbers, reduced regeneration of leukemic long-term hematopoietic stem cells in secondary transplant recipients, and enhanced survival of mice after discontinuation of treatment, in comparison with NIL alone. CML progenitors demonstrated enhanced sensitivity to Wnt stimulation, associated with increased expression of the FZD4 receptor. FZD4 knockdown inhibited CML progenitor growth. These results support further investigation of PORCN targeting to inhibit Wnt secretion and signaling and enhance targeting of CML stem cells while sparing their normal counterparts.